Time and position resolution of high granularity, high counting rate MRPC for the inner zone of the CBM-TOF wall - Petriş, Mariana; Bartoş, D.; Caragheorgheopol, G.; Deppner, Ingo Martin; Frühauf, J.; Herrmann, Norbert; Kiš, M.; Loizeau, P.-A.; Petrovici, M.; Rădulescu, L.; Simion, V.; Simon, Christian (Journal of Instrumentation, 2016)
Multi-gap RPC prototypes with a multi-strip-electrode readout were developed for the small polar angle region of the CBM-TOF subdetector, the most demanding zone in terms of granularity and counting rate. The prototypes are based on using low resistivity (∼ 1010 Ω·cm) glass electrodes for performing in high counting rate environment. The strip width/pitch size was chosen such to fulfill the impedance matching with the front-end electronics and the granularity requirements of the innermost zone of the CBM-TOF wall. The in-beam tests using secondary particles produced in heavy ion collisions on a Pb target at SIS18—GSI Darmstadt and SPS—CERN were focused on the performance of the prototypes in conditions similar to the ones expected at SIS100/FAIR. An efficiency larger than 98% and a system time resolution in the order of 70-80 ps were obtained in high counting rate and high multiplicity environment.